Temporal changes in Plasmodium falciparum anti-malarial drug sensitivity in vitro and resistance-associated genetic mutations in isolates from Papua New Guinea - Koleala, T.; Karl, S.; Laman, M.; Moore, Brioni; Benjamin, J.; Barnadas, C.; Robinson, L.; Kattenberg, J.; Javati, S.; Wong, R.; Rosanas-Urgell, A.; Betuela, I.; et al. (BioMed Central, 2015)
Background: In northern Papua New Guinea (PNG), most Plasmodium falciparum isolates proved resistant to chloroquine (CQ) in vitro between 2005 and 2007, and there was near-fixation of pfcrt K76T, pfdhfr C59R/S108N and pfmdr1 N86Y. To determine whether the subsequent introduction of artemisinin combination therapy (ACT) and reduced CQ-sulphadoxine-pyrimethamine pressure had attenuated parasite drug susceptibility and resistance-associated mutations, these parameters were re-assessed between 2011 and 2013. Methods: A validated fluorescence-based assay was used to assess growth inhibition of 52 P. falciparum isolates from children in a clinical trial in Madang Province. Responses to CQ, lumefantrine, piperaquine, naphthoquine, pyronaridine, artesunate, dihydroartemisinin, artemether were assessed. Molecular resistance markers were detected using a multiplex PCR ligase detection reaction fluorescent microsphere assay. Results: CQ resistance (in vitro concentration required for 50% parasite growth inhibition (IC50) >100 nM) was present in 19% of isolates. All piperaquine and naphthoquine IC50s were <100 nM and those for lumefantrine, pyronaridine and the artemisinin derivatives were in low nM ranges. Factor analysis of IC50s showed three groupings (lumefantrine; CQ, piperaquine, naphthoquine; pyronaridine, dihydroartemisinin, artemether, artesunate). Most isolates (96%) were monoclonal pfcrt K76T (SVMNT) mutants and most (86%) contained pfmdr1 N86Y (YYSND). No wild-type pfdhfr was found but most isolates contained wild-type (SAKAA) pfdhps. Compared with 2005-2007, the geometric mean (95% CI) CQ IC50 was lower (87 (71-107) vs 167 (141-197) nM) and there had been no change in the prevalence of pfcrt K76T or pfmdr1 mutations. There were fewer isolates of the pfdhps (SAKAA) wild-type (60 vs 100%) and pfdhfr mutations persisted. Conclusions: Reflecting less drug pressure, in vitro CQ sensitivity appears to be improving in Madang Province despite continued near-fixation of pfcrt K76T and pfmdr1 mutations. Temporal changes in IC50s for other anti-malarial drugs were inconsistent but susceptibility was preserved. Retention or increases in pfdhfr and pfdhps mutations reflect continued use of sulphadoxine-pyrimethamine in the study area including through paediatric intermittent preventive treatment. The susceptibility of local isolates to lumefantrine may be unrelated to those of other ACT partner drugs. Trial registration: Australian New Zealand Clinical Trials Registry ACTRN12610000913077.